A pure magnetite hydrogel: synthesis, properties and possible applications. Issue 45 (8th November 2017) - Anastasova, Elizaveta I.; Ivanovski, Vladimir; Fakhardo, Anna F.; Lepeshkin, Artem I.; Omar, Suheir; Drozdov, Andrey S.; Vinogradov, Vladimir V.
Abstract : A magnetite-only hydrogel was prepared for the first time by weak base mediated gelation of stable magnetite hydrosols at room temperature. Abstract : A magnetite-only hydrogel was prepared for the first time by weak base mediated gelation of stable magnetite hydrosols at room temperature. The hydrogel consists of 10 nm magnetite nanoparticles linked by interparticle Fe–O–Fe bonds and has the appearance of a dark-brown viscous thixotropic material. The water content in the hydrogel could be up to 93.6% by mass while volume fraction reaches 99%. The material shows excellent biocompatibility and minor cytotoxic effects at concentrations up to 207 μg mL −1 . The gel shows excellent sorption capacity for heavy metal adsorption such as chrome and lead ions, which is 225% more than the adsorption capacity of magnetite nanoparticles. Due to thixotropic nature, the gel demonstrates mechanical stimuli-responsive release behavior with up to 98% release triggered by ultrasound irradiation. The material shows superparamagnetic behavior with a coercivity of 65 emu g −1 at 6000 Oe. The magnetite gels prepared could be used for the production of magnetite aerogels, magnetic drug delivery systems with controlled release and highly efficient sorbents for hydrometallurgy.